1984
DOI: 10.1099/0022-1317-65-3-663
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of L and NS Proteins of Vesicular Stomatitis Virus with its Template Ribonucleoprotein during RNA Synthesis in vitro

Abstract: SUMMARYSoluble transcriptase containing the L and the NS proteins was isolated from purified vesicular stomatitis virus and its binding with the template ribonucleoprotein containing the N protein-RNA complex was studied with respect to its ability to initiate and synthesize RNA in vitro. By using u.v.-irradiated template reconstituted with soluble transcriptase, it was shown that the synthesis of leader RNA and other small initiated mRNA sequences continued while full-length mRNA synthesis decreased by 90~. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The interpretation of these results is that lowering the salt increases de novo polymerase initiations, and since the polymerases can bind directly only to the 3' end, only AC synthesis is increased. However, when Thornton et al (1984) repeated the reconstitution experiments with an AC reaction, they found both leader and mRNA starts, although 60% of the label in the "m RNA" oligonucleotide band was in sequences corresponding to neither leader nor mRNA. Until further experiments are done, there is no convincing way to reconcile the aforediscussed data, and it may be useful to review numerous caveats.…”
Section: Transcription Modelsmentioning
confidence: 94%
“…The interpretation of these results is that lowering the salt increases de novo polymerase initiations, and since the polymerases can bind directly only to the 3' end, only AC synthesis is increased. However, when Thornton et al (1984) repeated the reconstitution experiments with an AC reaction, they found both leader and mRNA starts, although 60% of the label in the "m RNA" oligonucleotide band was in sequences corresponding to neither leader nor mRNA. Until further experiments are done, there is no convincing way to reconcile the aforediscussed data, and it may be useful to review numerous caveats.…”
Section: Transcription Modelsmentioning
confidence: 94%
“…Internal transcription initiation has been long suggested for VSV (31,32), and more recently, VSV replication and transcription were shown to be initiated at different positions on the VSV genome (35). Polymerase complexes with different protein contents that are active either in replication or in transcription have been described (17).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such a virion-associated replicase can be established by purification of the associated protein components (L, P, and N) from the RNP. (iii) The multiple initiation of RNA (leader RNA and mRNA) observed during transcription (30,31) is, thus, carried out by two polymerase entities, replicase and transcriptase, respectively, and both must initially be located on the leader template at separate promoter sites. Recent observations, in fact, tend to support these contentions (7a, 18, 32; S. P. Whelan and G. W. Wertz, 20th Annu.…”
Section: Vol 77 2003 Notes 735mentioning
confidence: 99%